2019
DOI: 10.1177/1461348419850921
|View full text |Cite
|
Sign up to set email alerts
|

Car body floor vibration of high-speed railway vehicles and its reduction

Abstract: An on-site test has been performed to address the problem of feet numbness caused by the floor vibration of high-speed railway vehicles. Analysis of the floor vibration performance indicates that the vibration of the car body chassis transmitted to the floor by the elastic supports is significantly amplified in the frequency range of 20-50 Hz. This overlaps with the frequency range in which human lower extremities are most sensitive, leading to feet numbness. A refined finite element model of the car body, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…e design documents of the high-speed train establish the three-dimensional solid model and import it into the finite element analysis software while the material properties, such as Poisson ratio, elastic modulus, density, yield strength, and tensile strength, are set [21]. Table 4 displays the specific values.…”
Section: Finite Element Simulation Of Gearbox Shell Structurementioning
confidence: 99%
“…e design documents of the high-speed train establish the three-dimensional solid model and import it into the finite element analysis software while the material properties, such as Poisson ratio, elastic modulus, density, yield strength, and tensile strength, are set [21]. Table 4 displays the specific values.…”
Section: Finite Element Simulation Of Gearbox Shell Structurementioning
confidence: 99%
“…A v is roughness constant and equal to 4:032 × 10 À7 ðm:radÞ V c and V r are cutoff spatial frequency; these constants are equal to 0:8246 (rad/m), 0:0206 (rad/m), respectively. On the vehicle wheel, this irregularity in the frequency domain, at the running speed of v (m/s), can be accounted for by using equation (17). 6 SðωÞ ¼…”
Section: Track Irregularitymentioning
confidence: 99%
“…Wang et al (2019) 16 proposed to use active suspension with control delay to improve the ride comfort of road vehicles. Gong et al (2019) 17 reported a problem of feet numbness induced by the floor vibration of a high-speed train. They reduced the carbody floor vibration by optimizing the elastic supports of the under-chassis equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, yet few studies have been reported on the vibration controlling of an EMU floor. The methods of vibration controlling applied to train floors are mostly empirical, such as modifying the location and extent of the support structure between the inner floor and the structural floor [4,[10][11][12][13][14], or using high-damping material [14]. Hudson et al [15] performed a multiple objective optimization to minimize the mass and cost of composite sandwich panels for the interior floor structure of a metro car.…”
Section: Introductionmentioning
confidence: 99%